HUBUNGAN PENGETAHUAN IBU, POLA KONSUMSI DAN DIET BGBC DENGAN STATUS GIZI ANAK AUTIS DI SEKOLAH LUAR BIASA (SLB) NEGERI KOTA SEMARANG TAHUN 2017 - Zakiyah Islamiaty Oktaviani; Sri Achadi Nugraheni; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Children with autism have disgestive disorders making it difficult do digest protein of gluten and casein, so it is very important for mothers to pay attention to their children and control their GFCF (Gluten Free Casein Free) diet. The aim of this study was to analyze the association between mother’s knowledge, consumption pattern and GFCF diet with nutritional status of children with autism in special school Semarang. The design of this study was cross sectional study with quantitative research method. The study samples were 52 childrens with autism and their mother based on the inclusion criteria. Data was analyzed using Kolmogorov-Smirnoff Test, Rank Spearmann Test and Pearson Product Moment Test. The result showed there were 57,7% mothers had good knowledge, 100% of childrens with autism still consumed foods that contain gluten casein there are macaroni (67,3%) and butter (75%), there are 61,5% childrens were normal, 19,2% were fat, 15,4% were obesity, 3,8% were lean based on body mass index per age, 88,5% were normal, 7,7% were short, 3,8% were very short based on height per age, 58% had good nutritional status and 42% had over nutritional status based on weight per age. Rank Spearmann Test result showed there is on correlation between mother’s knowledge (p>0,05) with nutritional status (p=0,667, 0,563, 0,491), and between mother’s knowledge with consumption pattern (p=0,296) and Pearson Product Moment Test result showed there is on correlation between consumption pattern with nutritional status (p=0,308, 0,113, 0,609). It can be concluded there is on correlation between mother’s knowledge, consumption pattern and GFCF Diet with nutritional status of children with autism in special school Semarang 2017.